Downsizing as a sorting device. Are low-productive workers more likely to leave downsizing firms? - Morten Henningsen; Torbjørn Hægeland (Statistics Norway, Research Department, 2008)
Employers cannot always displace workers at their own discretion. In many countries, Employment Protection Legislation (EPL) includes restrictions on laying off workers. This paper studies whether employers use downsizing events, where the rules for dismissal differ from the rules that apply for individual dismissal, to displace workers selectively. We investigate empirically whether workers with low expected productivity relative to co-workers face particularly high exit risks when establishments downsize. Our evidence is consistent with establishments using downsizings as a sorting device to terminate the employment of the least profitable workers who are protected against dismissal under normal times of operation. However, only a minor share of the displacements in downsizings may be attributed to opportunistic sorting by employers, suggesting that EPL may not be an important obstacle to firms' firing of individual workers.
Keywords: I18; J63; J65; 330; Downsizing; sickness absence; employment protection